Hubungan Screen Time Dengan Kecerdasan Emosional ada Siswa SMP Dr Soetomo Surabaya - Giovanni Owen Nanda Wijaya; Wahyu Prasasti Mutiadesi; Rahadianto (Journal of Health Educational Science And Technology, 2024)
The utilization of screen time among adolescents, especially 8th-grade students at Dr. Soetomo Junior High School in Surabaya, has become an inevitable phenomenon significantly impacting the development of emotional intelligence. This research aims to comprehend the relationship between screen time and students' emotional intelligence. Employing a quantitative approach and a cross-sectional design, the study identifies a positive and significant correlation between screen time and students' emotional intelligence, with a Spearman correlation coefficient of 0.842. These findings highlight the pivotal role of screen time management in supporting the development of emotional intelligence during this critical developmental stage. Recommendations include intensive supervision of screen-based activities, understanding the selection of positive activities, and further research involving additional variables for a more holistic understanding.